Seismic performance evaluation of damage-controlled composite steel frame with flexible-gel-covered studs. (15th September 2020) - Zeng, Xianzhi; Deng, Kailai; Kurata, Masahiro; Duan, Jiahong; Zhao, Canhui
Highlights: Using FGC studs maintains the overall mechanical performance of the whole steel frame; One-third conventional shear studs in the middle zone were necessary for a reliable shear force transfer; The FGC studs provided the best damage control for the slab under small to moderate deformation or ground motion intensity. Abstract: This paper proposes flexible-gel-covered (FGC) studs to reduce the earthquake damage of a concrete slab in a composite steel frame. With the FGC studs in the novel frame, the shear constraint between the steel beam and the concrete slab was intentionally released, and the tensile strain of the slab decreased under a positive moment when the initial objective was achieved. To verify the utility of FGC studs in damage control, a numerical model was developed in ABAQUS. The performance of one single composite beam was investigated to obtain the optimal configuration of the FGC studs. Based on single beam analysis, two steel frames were modeled using ABAQUS, including one conventional frame and one novel steel frame with FGC studs. Pushover analysis and nonlinear dynamic analysis were carried out. The numerical simulation results revealed that the overall structural performance of the novel frame with FGC studs was adequately maintained compared with a conventional steel frame, which demonstrates the direct applicability of the current seismic design approach. The performance of the FGC stud and its effective range for damage reduction are discussed in detail. The FGC studs are beneficial in terms of reducing the local slab damage under small to moderate earthquakes. Under strong earthquake, the efficiency decreased for very large story drift.